PENGARUH PEMBERIAN TABLET BESI DAN VITAMIN E PADA KADAR HEMOGLOBIN DAN STATUS BESI WANITA USIA SUBUR YANG DIDUGA MENDERITA THALASEMIA KARIER - M. Saidin; Sukati Sukati; Muherdiyatiningsih Muherdiyatiningsih; Effendi Rustan (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2003)
THE EFFECT OF IRON PILL SUPPLEMENTATION ADDED WITH VITAMIN E (ALPHA-TOCOPHEROL) TO HEMOGLOBIN AND IRON STATUS OF CHILDBEARING AGE WOMEN SUSPECTED SUFFERING FROM CARRIER THALASSEMIA.Background: Anemia control programme among pregnant women had been conducting for about three decades, but prevalence of anemia still considered high. It was reported by Nutrition and Food Research Centre (2000) that 37.4% of childbearing women indicated fragility of red blood cell membrane wich assumed related to anemia. One of the vitamins which have positive effect to the wall of red blood cells is vitamin E through its rolle as antioxidant. It was recommended to conduct a study to determine the effect of supplementation of iron pill, "Ferro sulfate" (60 mg elemental iron with 25 mg folic acid) added with vitamin E (20 mg a-tocopherol) to hemoglobin level and iron status of childbearing age of women.Methods: The study design was "Intervention with quacy experiment trial".  The study sites covered 10 villages in Cianjur district of West Java. A total of 210 childbearing age women (19-45 years old) with indication of fragility of red blood cell membrane which was determined by procedure of NESTROF (Naked Eye Single Test Tube Red Cell Osmotic Fragility), divided into two groups (105 women/group). Group I received one iron pill daily and vitamin E twice a week for 10 weeks. While group II received Iron pill only, without vitamin E. Data collection was conducted before and after intervention.Results: After 10 weeks intervention, the average of Hb increament of group I (0.4 g/dl) was slightly higher than that of group II (0.3 g/dl). There was improvement of serum ferritin of both groups with increament 4.3 mg/dl for group I and 7.2 mg/dl for group II. Vitamin E status of both groups still considered low: 3.1 mg/L for group I and 3.1 mg/L for group II. Normal value of serum vitamin E is 5.0 mg/L.Conclusions: Vitamin E (20 mg of a-tocopherol) which was given twice a week bisides daily supplementation of iron pill (60 mg elemental iron of sulfas ferrosus + 25 mg folic acid) for 10 weeks increased the effectiveness of Hb synthesis 1.5 times than that of supplementation of iron only without vitamin E.Keywords: iron supplementation, Hb level, iron status, vitamin E status, NESTROF, fragility of cells membrane